A new methyl-embedded (3, 36)-connected txt-type metal–organic framework exhibiting high H2 adsorption property. Issue 23 (24th May 2017) - Du, Liting; Zhang, Jinchi; Lu, Zhiyong; Duan, Jingui; Xu, Li
Abstract : A new methyl-embedded (3, 36)-connected txt -type metal–organic framework was successfully synthesized and it exhibits high H2 uptake capacity. Abstract : A new methyl-embedded (3, 36)-connected txt -type metal–organic framework, Cu2 (DCPEMP)·H2 O n (NJFU-4, H4 DCPEMP = 3, 5-bis(3, 5-dicarboxylphenylethynyl)-4-methylpyridine), was solvothermally synthesized and structurally characterized, which exhibits a BET surface area of 2160 m 2 g −1, high stability and high H2 uptake capacity (2.61 wt% at 1 bar and 77 K).